Exploration of Implicit Culture Belief among English Major Students in China - Ruiyang , Ren; Hassan, Hanita (Journal of Ecohumanism, 2024)
This study aims to explore English major students’ implicit culture belief and factors influencing such beliefs within a limited intercultural environment in China. A total of 369 Year 3 and 4 English major students at Hebei International Studies University were surveyed through a mixed-method approach involving a survey questionnaire and semi-structured interviews. The study utilized the adapted Implicit Culture Belief Scale and a self-designed demographic questionnaire. The results displayed that English major students’ implicit culture beliefs tend to entity beliefs, namely fixed and unchangeable judgement on cultural attributes such as cultural values like individualism-collectivism and personality traits like extraversion-introversion in their implicit culture beliefs within the constrained intercultural settings. Furthermore, the factors influencing English major students’ entity beliefs in implicit culture belief include socio-cultural environment, media and psychological inclination toward stability. This investigation underscores students' cognitive process of cultural attributes to delve into their internal cognitive mechanisms regarding cultural values and personality traits within the limited intercultural milieu in China.